Emergence of IncX3 Plasmid-Harboring blaNDM–5 Dominated by Escherichia coli ST48 in a Goose Farm in Jiangsu, China - Liu, Ziyi; Xiao, Xia; Li, Yan; Liu, Yuan; Li, Ruichao; Wang, Zhiqiang (Frontiers in Microbiology, 2019)
Twelve carbapenem-resistant E. coli strains were obtained from goose farms in Jiangsu, China. These isolates were resistant to multiple antimicrobials, and positive for the blaNDM-5. The carbapenem-resistance of all strains mediated by blaNDM-5 were successfully conjugated to E. coli J53. S1-PFGE and WGS results showed blaNDM-5 was located on IncX3 conjugative plasmids with a size of ca. 46kb. All blaNDM-5-bearing IncX3 plasmids shared the same genetic context almost identical to pNDM_MGR194-blaNDM-5 and pNDM-QD28-blaNDM-5 reported in India and China, respectively. The twelve strains belonged to three STs, in which the dominant type of E. coli isolated from breeding goose farm carrying blaNDM-5 was ST48. The emergence of blaNDM-5-bearing strains in goose farms and the clonal transmission of E. coli within the breeding goose farm highlighted the potential reservoir of carbapenemase genes in waterfowl farming system, which may further contaminate environments and pose a threat to public health. Comprehensive surveillance of carbapenem-resistant bacteria in goose farms warrants further study to evaluate the underlying risks.